A New Voltammetric Approach for the Determination of Biomimetic Catalyst Kinetic Constants Based on Substrate Consumption. Issue 3 (12th August 2022) - Mikysek, Tomáš; Frühbauerová, Michaela; Švancara, Ivan; Novák, Miroslav; Sýs, Milan
Abstract: In the present study, a new voltammetric method is introduced for the determination of kinetic parameters of artificial metalloenzymes (biomimetic complexes) mimicking the catecholase activity towards 3, 5‐di‐ tert ‐butylcatechol (3, 5‐DTBC) or 2, 5‐di‐ tert ‐butylhydroquinone, and representing a promising alternative to common spectrophotometric method. To demonstrate the effectiveness of the electrochemical approach, two binuclear copper(II) complexes bearing the same pentadentate ligand and different ionic ligands were selected. Apparent kinetic parameters, such as maximum velocity ( V max ), Michaelis‐Menten constant ( K m ), and turnover number ( k cat ), obtained by the described method employing differential‐pulse voltammetry were in good agreement with the data evaluated from UV‐Vis spectrophotometric measurements. Abstract :